Penerapan Customer Relationship Management (CRM) pada Aplikasi Pengiriman Pesan Instan Studi Kasus: WhatsApp, WeChat, Line, KakaoTalk - Ellynia Ellynia; Viany Utami Tjhin (ULTIMA InfoSys, 2014)
In establish good relationship with customer, companies need to have a good customer relationship management system as well. The purpose of this study is to explore the level of development of the use of instant messaging applications that are used for mobility of companies in establishing relationships with customers; and to investigate the factors considered important for the success of the mobility of companies in establishing relationships with their customers. In this study it was found that not all instant messaging application has a feature which serves to establish rapport with customers. The results showed some of the determinants of success in the utilization of instant messaging applications is the ease of use, target the most used mobile devices, operating systems most used by users, and mobile application user interface that is used. Index Terms - customer, relationship, management, application, messanging, instant